DOES TRANSFORMATIONAL LEADERSHIP AFFECTING THE INNOVATIVE SKILLS OF STUDENTS? - Mamat Rahmatullah; Atika Atika (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2021)
This research aims to determine the influence of transformational leadership on innovative behavior through psychological empowerment as a mediation variable. This study used quantitative methods. The data collected by interviews and questionnaires. The samples were taken using a saturated model from 42 responden of student association of Islamic Education Management Study Program, UIN Sulthan Thaha Saifuddin Jambi. The data were analyzed using descriptive, regression, and path analysis. The results showed that transformational leadership significantly influenced students' innovative behavior directly or mediated by psychological empowerment variables. The resulting impact of pathway coefficients on psychological empowerment has a considerable effect on the innovative behavior of students with a p-values value of 0.003 < from 0.05; transformational leadership has a substantial impact on innovative behavior through psychological empowerment with a p-values value of 0,000 > 0.05. It shows that improving students' innovative behavior can be achieved with transformational leadership roles through psychological empowerment variable in student association of Islamic Education Management Study Program, UIN Sulthan Thaha Saifuddin Jambi. The association of students are expected to pay attention to students needs and activities, create a comfortable organizational environment to optimizing student activities.